The Development of Blended Leaning by Using the Design Thinking Method to Enhance Information, Media, and Technology Skills for Computer Education Students at Rajabhat University in Thailand: A Systematic Literature Review - Kaiyasith Apirating, Charinthorn Aumgri, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The purpose of this research was to do a systematic literature review (SLR) on the development of blended learning by using the design thinking method to enhance information, media, and technology skills for computer education students at Rajabhat University in Thailand. The study included 68 topics from related books, research, articles, and documents both in and outside Thailand. The SLA started from the blended method including 50% face-to-face learning and 50% online learning whereas the design thinking method consisted of 5 steps of the BDL-DTM Model developed through the assessment of 9 experts. The 5 steps of the BDL-DTM Model were 1) empathize, 2) define, 3) ideate, 4) prototype, and 5) test. The resulting model supported the computer education at Rajabhat University in Thailand for promoting their information, media, and technology skills. The students who studied with the BDL-DTM Model can further develop the method in their research and classroom teaching.